Memória e tradição no romance A Varanda do Frangipani, de Mia Couto - Mascena, Suelany Christtinny Ribeiro (2011)
The present work, result of our incursion through Mia Couto s work, discusses the manifestations of orality, in riddles and proverbs, and death in the novel Under The Frangipani, contributing as key elements to the preservation of African memory and traditions. For this research we rely on several authors, we quote some such as Maurice Halbwachs (2009), Henri Bergson (2006), Hampatê Bâ (1983) and Andre Jolles, they perform relevant studies about memory, orality and forms that compose them. Besides those authors, we researched scholars like Frantz Fanon (2008), Aimé Césaire (1978) and Homi Bhabha (2007) in order to delve into the causes and consequences generated by colonialism and postcolonialism. About Mozambique's history, the colonial and civil wars, we based our study on Peter Fry (2001) and José Luis Gourds (2009), because it was during such events, that the Portuguese-speaking African literatures, especially in Mozambique, assumed defining characteristics. It is from this background that the author Mia Couto weaves his narratives and confirms the use of literature as an instrument of identity, memory and tradition of his country.